2007
DOI: 10.1105/tpc.106.045708
|View full text |Cite
|
Sign up to set email alerts
|

Rice SCAMP1 Defines Clathrin-Coated,trans-Golgi–Located Tubular-Vesicular Structures as an Early Endosome in Tobacco BY-2 Cells

Abstract: We recently identified multivesicular bodies (MVBs) as prevacuolar compartments (PVCs) in the secretory and endocytic pathways to the lytic vacuole in tobacco (Nicotiana tabacum) BY-2 cells. Secretory carrier membrane proteins (SCAMPs) are post-Golgi, integral membrane proteins mediating endocytosis in animal cells. To define the endocytic pathway in plants, we cloned the rice (Oryza sativa) homolog of animal SCAMP1 and generated transgenic tobacco BY-2 cells expressing yellow fluorescent protein (YFP)-SCAMP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
370
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 270 publications
(398 citation statements)
references
References 88 publications
(141 reference statements)
24
370
2
2
Order By: Relevance
“…This is deduced from the lack of co-localization between AtSNX1-mRFP or YFP-BP80 and specific markers of GNOM endosomes and the TGN, and by the insensitivity of these organelles to Wm. Interestingly, in contrast to our observations, Lam et al (2007) recently reported that, in tobacco BY-2 cells, the PVC/MVB is not found in BFA compartments, although it is sensitive to Wm, and that the TGN fuses to the PVC/MVB after Wm treatment. This discrepancy between our data and those of Lam et al underlines the variability that endomembrane systems may display depending on cell types.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This is deduced from the lack of co-localization between AtSNX1-mRFP or YFP-BP80 and specific markers of GNOM endosomes and the TGN, and by the insensitivity of these organelles to Wm. Interestingly, in contrast to our observations, Lam et al (2007) recently reported that, in tobacco BY-2 cells, the PVC/MVB is not found in BFA compartments, although it is sensitive to Wm, and that the TGN fuses to the PVC/MVB after Wm treatment. This discrepancy between our data and those of Lam et al underlines the variability that endomembrane systems may display depending on cell types.…”
Section: Discussioncontrasting
confidence: 55%
“…Recently, the TGN was reported to be the first compartment labelled with FM4-64 in Arabidopsis root cells (Dettmer et al, 2006). This was confirmed in cultured tobacco BY-2 cells (Lam et al, 2007). Whether FM4-64 transits first through AtSNX1 endosomes to then reach the TGN or directly accumulates in the TGN without trafficking via endosomal structures remains an unsolved question.…”
Section: Position Of the Pvc/mvb In The Endosomal Pathway In Arabidopmentioning
confidence: 85%
See 2 more Smart Citations
“…YFP fusions of plant SCAMPs have been localized to many endomembrane compartments, including EE, PM, secretory vesicles and the cell plate [58,59]. Moreover, ES1 treatment showed that trafficking of SCAMP1 in Arabidopsis is TGN dependent (Figure 4F), validating its colocalization with SYP61 in TGN vesicles.…”
Section: Syp61 Facilitates the Trafficking Of Proteins To The Pmmentioning
confidence: 61%